EL uso de material didáctico para mejorar el desarrollo lingüístico de los niños de 4 a 5 años del centro de educación inicial Hugo Guillermo González paralelo “a” de la ciudad de Loja período 2017-2018. - Chocho Calva, Maria Valeria (2018)
The present investigation was framed in a scientific and experimental study on the topic: THE USE OF TEACHING MATERIAL TO IMPROVE THE LINGUISTIC DEVELOPMENT OF CHILDREN FROM 4 TO 5 YEARS OF THE "HUGO GUILLERMO GONZÁLEZ" INITIAL EDUCATION CENTER PARALLEL "A" IN THE CITY OF LOJA, ACADEMIC YEAR-PERIOD 2017-2018, the general objective of this research study was aimed at determining the incidence of the use of didactic material to improve the linguistic development of children from 4 to 5 years of the Initial Education Center "Hugo Guillermo González" Parallel " A "from the city of Loja, academic year-period 2017-2018. The methods used were as follows: the scientist, analytical - synthetic, inductive-deductive and statistical. The techniques used for both children and teachers were the observation card, and the instrument was the Articulation Test for Repetition. Such a test was administered to the 21 children, obtaining the following results: 100 percent of the population omit and replace some phonemes, and about 10 percent of the children distort them. And finally, regarding the phonological aspect, 100 percent of the research sample had not consolidated it. Hence, a proposal "Developing my language" was elaborated and developed, and it was validated through a post-test. The test results show that 52 percent of the 21 children decreased the omission of the phonemes, 38 percent did not substitute them and 95 percent did not distort the phonemes at the time of speaking. In the phonological aspect, 33 percent of children achieved consolidated learning, 38 percent of them were in process, and 29 percent of them presented initial learning. It was concluded that the established proposal is valid since it evidenced improvement in the language of children in terms of the production of phonemes, such as omission, substitution and distortion and consequently, it is recommended to continually stimulate the language of children in initial education, through activities that include didactic material